2022
DOI: 10.1038/s41380-022-01848-5
|View full text |Cite
|
Sign up to set email alerts
|

Hypodopaminergic state of the nigrostriatal pathway drives compulsive alcohol use

Abstract: The neurobiological mechanisms underlying compulsive alcohol use, a cardinal feature of alcohol use disorder, remain elusive. The key modulator of motivational processes, dopamine (DA), is suspected to play an important role in this pathology, but its exact role remains to be determined. Here, we found that rats expressing compulsive-like alcohol use, operationalized as punishment-resistant self-administration, showed a decrease in DA levels restricted to the dorsolateral territories of the striatum, the main … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 95 publications
2
5
0
Order By: Relevance
“…A tolerance to the DA-elevating effect of cocaine in the nucleus accumbens has previously been observed via microdialysis using both short- [58,59,73] and long-access [74,75] schedules of cocaine SA, and it is viewed as a critical determinant in the development of drug dependence and addiction [76]. Our results extend this effect to the dorsal striatum, where hypodopaminergic functioning has been linked to compulsive drug use [77]. Moreover, we showed that this tolerance was baseline-dependent, and it correlated negatively with baseline levels of AMPH-induced DA overflow, suggesting a floor effect of cocaine exposure in reducing evoked DA release.…”
Section: Discussionsupporting
confidence: 79%
“…A tolerance to the DA-elevating effect of cocaine in the nucleus accumbens has previously been observed via microdialysis using both short- [58,59,73] and long-access [74,75] schedules of cocaine SA, and it is viewed as a critical determinant in the development of drug dependence and addiction [76]. Our results extend this effect to the dorsal striatum, where hypodopaminergic functioning has been linked to compulsive drug use [77]. Moreover, we showed that this tolerance was baseline-dependent, and it correlated negatively with baseline levels of AMPH-induced DA overflow, suggesting a floor effect of cocaine exposure in reducing evoked DA release.…”
Section: Discussionsupporting
confidence: 79%
“…Individuals with greater midbrain D3 receptors may have lower phasic dopamine release particularly in response to rewards which leads to poorer value updating and, therefore, a lower Δ + parameter. Indeed, a hypodopaminergic state has been proposed to be a risk factor for addiction (Goutaudier et al, 2022; Kótyuk et al, 2022) and associated with poor decision making (Rutledge et al, 2009, 2015; Clarke et al, 2011; Costa et al, 2015). Midbrain D3 receptors may, therefore, be at the nexus between addiction susceptibility and decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, unlike one gene-one disease (OGOD), RDS is polygenetic and complex. Even though the genes selected for GARS are not the only ones associated with all addictive behaviors, we decided to focus on specific reward genes, and associated polymorphisms were chosen based on hypodopaminergia [ 79 ]. Other genes, such as alcohol metabolism genes (e.g., alcohol dehydrogenase) combined with GARS, may provide an even stronger association in terms of addiction vulnerability.…”
Section: Genetic Addiction Risk Severity (Gars)mentioning
confidence: 99%